Estudio de factibilidad para la implementación de una empresa que comercialice y haga el montaje de pisos eléctricos en la ciudad de Bogotá D.C. (2020)
In this project, a feasibility study was carried out for the implementation of a company that markets and assembles electrical floors in the city of Bogotá D.C. To start, an analysis of the energy sector was carried out, opportunities and aspects that might or might not impact the development of the project as well as the first impression of the feasibility or not of this were evaluated. A market study was carried out, evaluating in these factors such as the target market, the preferences, tastes, acceptance and motivation of the market to want to implement the product and service that is being offered, as well as strategies for marketing mix for the company.